Restorative Justice-Based Criminal Case Resolution: A Study at Restorative Justice Houses in Yogyakarta - Cahya Wulandari; Lutvi Tri Cahyanto; Winarsih; Derita Prapti Rahayu; Muhamad Sayuti Hassan (IJCLS (Indonesian Journal of Criminal Law Studies), 2025)
The retributive paradigm in criminal case resolution focuses on punishing the offender, often neglecting the victim's interests. This is evident in victims' limited role in court, where they primarily serve as witnesses and lack the authority to take meaningful action. Furthermore, the Indonesian legal system continues to prioritize imprisonment, resulting in incarceration for nearly all offenses, ranging from minor to severe, which contributes significantly to prison overcrowding. This study examined and analyzed the role of Restorative Justice Houses in Yogyakarta City in resolving criminal cases through a restorative justice approach. Such an approach is crucial, as it promotes social harmony and helps prevent larger societal conflicts. Therefore, it is essential to advocate for the broader implementation of restorative justice as a conflict resolution.